Mater Sempre Certa Est – Should We Register Transsexual Woman-to-Man as a Father? Remarks on the ECHR Judgment O.H. and G.H. v. Germany - Pirošíková, Marica; Fialová, Jitka; Zdechovský, Tomáš (Review of European and Comparative Law, 2024)
The study is designed as an in-depth interdisciplinary report of the case O.H. and G.H. against Germany, which was analyzed by the European Court of Human Rights in Strasbourg (ECHR). The authors explain why the best interest of the child should prevail over the interests of a trans man, who gave birth to a child and requests to be registered as the father of the child. One of the reasons is mater semper certa est, a universally known principle of Roman law stating that “the mother is always certain” and no counterevidence can be made against this principle. In this regard, the best interest of the child and the child’s right to know his or her origin shall be observed. There are also several other life areas, that would be negatively impacted by breaking this principle.